"Clause and effect": Invention and state intervention during the French Revolutionary and Napoleonic Wars - Stephen D. Billington; Joe Lane (Queen's University Centre for Economic History (QUCEH), 2023)
Did the outbreak of the French Revolutionary and Napoleonic Wars influence technical change during the Industrial Revolution? We address this question by investigating an instance of state intervention into the market for inventions from 1793-1820: the introduction of a new proviso into British patents compelling inventors to supply the military, and also attracting military inventions from outside the patent system. We present new patent data alongside previously unused archival evidence to argue that the state's intervention helped direct technical change in Britain. Our evidence provides additional support for the military-demand-induced hypothesis as a credible explanation for Britain's ongoing industrialisation.
Keywords: N43; N73; O31; 330; Industrial Revolution; Institutions; Invention; Patents